Adrenal surgery in England: better outcomes in high‐volume practices. (15th February 2016) - Palazzo, Fausto; Dickinson, Andrew; Phillips, Barbara; Sahdev, Anju; Bliss, Richard; Rasheed, Ashraf; Krukowski, Zygmunt; Newell‐Price, John
Summary: Aims and Background: Adrenal surgery is performed by a variety of surgical specialities in differing environments and volumes. International data suggest that there is a correlation between adrenal surgery volume and outcomes but there are no UK data to support this or UK surgical guidelines. A multidisciplinary team representing the stakeholders in adrenal disease is preparing a national guidance on adrenal surgery. A review of the outcomes for adrenal surgery in England was performed to correlate outcomes with the volume of surgeon practice. Methods: Hospital Episode Statistics (HES) data for the National Health Service (NHS) in England in the tax year 2013–2014 were examined for adrenal surgery. Length of hospital stay and rate of postoperative readmission were assessed as surrogate quality markers and a comparison made between 'high‐' and 'low‐' volume surgeons. Results: A total of 795 adult adrenalectomies were performed by 222 different surgeons with a range of between 1 and 34 adrenalectomies performed per surgeon. Only thirty‐six (16%) adrenal surgeons performed 6 or more adrenalectomies. A total of 186 surgeons (84%) performed a median of one adrenalectomy a year. Length of stay and readmission rate within thirty days of operation was 60% longer and 47% higher, respectively, when performed by low‐volume surgeons. Conclusion: The current provision of adrenal surgery in the UK is not in the best interests of patients and is not cost‐effective for the NHS. Adrenal surgery is best performed by higher volume surgeons in centres with dedicated adrenal multidisciplinary teams expert in all aspects of care of the adrenal patient.